The Settlement of Travel Bureau Role in the Development of Medical Tourism in Indonesia - Aditya Putra Thama (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
The trend of development in tourism world from year to year has shown a very rapid growth. The tourism is developed with the approach of growth and equity of the economy for the welfare of the people and is oriented to the development of the region, relying on the community, and empowering the community covering various aspects, such as human resources, marketing, destinations, science and technology, cross-sectoral linkages, intergovernmental cooperation, empowerment of small businesses, and responsibility in the utilization of natural and cultural resources. One of the opportunities for the development of tourism industry is in the field of health, especially the development of medical tourism. The aim of study is to examine the regulations on the medical tourism and the role of the tourism travel agencies in the development of the medical tourism in Indonesia. The method to achieve these goals is normative study with juridical and statute approaches. The results of data analysis indicate that regulations regarding medical tourism in Indonesia are set in the Regulation of the Ministry of Health of the Republic of Indonesia Number 76 Year 2015 on Medical Tour Service. The role of travel agency in the development of the medical tourism is very strategic, starting from partners of the hospital in order to integrate the health services with lodging facilities and travel planning medical tours to conduct external promotions.